2022
DOI: 10.3390/vaccines10122099
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Regarding Monkeypox Virus among Physicians in Saudi Arabia: A Cross-Sectional Study

Abstract: The growing incidence of human monkeypox cases emphasizes the significance of prevention, early detection, and prompt responses for healthcare providers. The aim of this study was to assess the knowledge and attitudes toward monkeypox infection among physicians, a frontline healthcare worker group, in Saudi Arabia. A cross-sectional survey assessing knowledge and attitudes towards monkeypox infection on multiple-item scales was sent to physicians in Saudi Arabia. The associations between independent factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
53
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 31 publications
12
53
4
Order By: Relevance
“…Our study found that males possessed low levels of general knowledge about the monkeypox virus. Consistent with our research, Alshahrani et al achieved comparable results, reporting that female Saudi physicians had significantly better knowledge scores about the monkeypox virus than their male counterparts [ 18 ]. However, our study’s findings contradicted those of Sallam et al They observed that male HCWs were significantly more knowledgeable about monkeypox than their female counterparts [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that males possessed low levels of general knowledge about the monkeypox virus. Consistent with our research, Alshahrani et al achieved comparable results, reporting that female Saudi physicians had significantly better knowledge scores about the monkeypox virus than their male counterparts [ 18 ]. However, our study’s findings contradicted those of Sallam et al They observed that male HCWs were significantly more knowledgeable about monkeypox than their female counterparts [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to a WHO report, one of the obstacles in preventing the resurgence of monkeypox was a lack of knowledge about monkeypox, especially among healthcare workers (HCWs) [ 17 ]. Another recent study demonstrated that only 18.6% of HCWs reported having some knowledge of managing monkeypox [ 18 ]. Since Turkey is a popular tourist destination, physicians must be prepared and knowledgeable about cases of monkeypox to develop a global strategy to combat the emergence of monkeypox.…”
Section: Introductionmentioning
confidence: 99%
“…Mpox is generally a self-limited disease [ 5 ]. Its clinical presentation is comparable to but less severe than smallpox [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mpox is generally a self-limited disease [ 5 ]. Its clinical presentation is comparable to but less severe than smallpox [ 5 ]. Symptoms include fever, headache, muscle and back pain, fatigue, and skin rash, which can be very itchy and painful [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported lower levels of knowledge, such as Harapan et al, whose study revealed that 9.0% of physicians in Indonesia had good mpox knowledge when they used an 80% cutoff point, reaching a percentage of 36.5% when the cutoff was reduced to 70% [ 10 ]. On the other hand, Alshahrani et al reported that 55% of physicians had good knowledge of mpox in Saudi Arabia, a level that was considered poor by the authors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%